0 рейтинг
1 просмотр

9*(x-5)+4*(6-X)=3+3*(X+20)-2X

от (15 баллов) в разделе Математика | 1 просмотр

2 Ответов

0 рейтинг
Правильный ответ

9*(x-5)+4*(6-X)=3+3*(X+20)-2X

9х-45+24-4х=3+3х+60-2х

5х-21=х+63

5х-х=63+21

4х=84

х=84/4

х=21

от Архангел (150k баллов)
0 рейтинг

9*(x-5)+4*(6-x)=3+3*(x+20)-2x

9x-45+24-4x=3+3x+60-2x

9x-4x-3x+2x=3+60+45-24

4x=84

x=21

 

Проверка:

9*(21-5)+4*(6-21)=3+3*(21+20)-2*21

9*16+4*(-15)=3+3*41-2*21

144-60=3+123-42

84=84

от Начинающий (442 баллов)
10,984,878 заданий
13,471,016 решений
8,518,553 комментариев
4,909,216 пользователей